Analisis Konsep Keadilan Ekonomi dalam Pemikiran Ibnu Taimiyah: Relevansi terhadap Sistem Ekonomi Kontemporer - Ermiannur, Ermiannur; Siti Jumaidah; Neha Sartika; Dinda Ravina; Fitri Hayati (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the concept of economic justice according to Ibn Taimiyah and examine its relevance to the challenges of the modern economic system. Through a qualitative approach based on literature studies, it was found that principles such as honesty in trade, justice in the distribution of wealth, state involvement in maintaining market balance, and the prohibition of exploitation and monopoly are important foundations in Ibn Taimiyah's thinking. These values ​​have proven to remain contextual in facing the problems of global economic inequality, the dominance of large corporations, and the crisis of social justice in the modern era. The integration of the principles of ethics and justice promoted by Ibn Taimiyah is the key to building a more humane, inclusive, and sustainable economic order